2004
DOI: 10.1017/s0265021504000055
|View full text |Cite
|
Sign up to set email alerts
|

Rocuronium duration of action under sevoflurane, desflurane or propofol anaesthesia

Abstract: Desflurane anaesthesia significantly prolongs the duration of action of rocuronium at 0.9 mg kg(-1) single bolus dose, compared to sevoflurane or propofol anaesthesia maintenance regimens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 16 publications
0
9
1
Order By: Relevance
“…Inhalational anesthesia is more commonly used in clinical practice than intravenous anesthesia, so we used an inhalational anesthetic agent for anesthesia maintenance. However, although it remains equivocal [2728], the effect of sevoflurane on the recovery of a neuromuscular blockade by rocuronium cannot be completely ignored. In addition, one report suggested that sugammadex could not be affected by inhalational agents [29].…”
Section: Discussionmentioning
confidence: 99%
“…Inhalational anesthesia is more commonly used in clinical practice than intravenous anesthesia, so we used an inhalational anesthetic agent for anesthesia maintenance. However, although it remains equivocal [2728], the effect of sevoflurane on the recovery of a neuromuscular blockade by rocuronium cannot be completely ignored. In addition, one report suggested that sugammadex could not be affected by inhalational agents [29].…”
Section: Discussionmentioning
confidence: 99%
“…Because inhalation anesthesia is more widely used than intravenous anesthesia in clinical situations, we used sevoflurane in order to achieve a similar environment. However, sevoflurane delays the recovery from rocuronium compared with intravenous anesthesia [27], and tends to delay it but not significantly [28]. Even though this trial has been implemented in the same environment in each group, sevoflurane may have affected recovery from rocuronium.…”
Section: Discussionmentioning
confidence: 93%
“…Desflurane is a relatively new volatile anaesthetic, that have a low blood-gas solubility resulting in rapid uptake and elimination [10]. Its muscle-gas partition coefficient is lower than other volatile anaesthetics [11]. The enhancement of the neuromuscular blocking effects of muscle relaxants (both benzylisoquinoline and aminosteroid) by volatile anaesthetics is well known [11][12][13] and this phenomenon is called as "Potentiation" (10).…”
Section: Discussionmentioning
confidence: 99%
“…Its muscle-gas partition coefficient is lower than other volatile anaesthetics [11]. The enhancement of the neuromuscular blocking effects of muscle relaxants (both benzylisoquinoline and aminosteroid) by volatile anaesthetics is well known [11][12][13] and this phenomenon is called as "Potentiation" (10). Rocuronium bromide is a monoquaternary, aminosteroid, non-depolarising muscle relaxant with rapid onset and intermediate duration of action [10,13].…”
Section: Discussionmentioning
confidence: 99%